Aplikasi Metoda Taguchi Untuk Mengetahui Optimasi Kebulatan Pada Proses Bubut Cnc - Sidi, Pranowo; Wahyudi, Muhammad Thoriq (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
In this paper surface optimization for the surface roundness has been done by considering the cutting parameters as cutting speed, feed rate and depth of cut. The experiments were performed on a CNC lathe, and the materials used for the experiment is steel St.60, with 100 mm length and 1